2022
DOI: 10.1109/access.2022.3154103
|View full text |Cite
|
Sign up to set email alerts
|

Using the Methods of Statistical Data Analysis to Improve the Trustworthiness of Software Reliability Modeling

Abstract: In the past, many Software Reliability Growth Models (SRGMs) have been proposed to predict various aspects of software reliability and NHPP (Non-Homogeneous Poisson Process) based SRGMs have drawn a lot of attention. But it should be noted that, in practice, blindly applying SRGMs might not lead to meaningful results when the characteristics of data (i.e., data type) don't fit the characteristics of selected SRGM(s). Also, there does not exist any guidelines that project managers or developers can follow to se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…However, the foregoing discussion showed that most studies assume that software reliability growth behavior follows a non-homogeneous poisson process (NHPP), based on collected software failure data. It is worth noting that Hou [33] reported that before applying the failure data to the SRGMs, whether the dataset is of the NHPP type and whether it is used correctly by the NHPP-based SRGM should be explained. On the other hand, Kanoun and Lapire [4] also observed that the use of NHPP-based SRGMs during the early stages of development and validation is much less convincing.…”
Section: A Model-based Software Reliability Analysismentioning
confidence: 99%
“…However, the foregoing discussion showed that most studies assume that software reliability growth behavior follows a non-homogeneous poisson process (NHPP), based on collected software failure data. It is worth noting that Hou [33] reported that before applying the failure data to the SRGMs, whether the dataset is of the NHPP type and whether it is used correctly by the NHPP-based SRGM should be explained. On the other hand, Kanoun and Lapire [4] also observed that the use of NHPP-based SRGMs during the early stages of development and validation is much less convincing.…”
Section: A Model-based Software Reliability Analysismentioning
confidence: 99%